EFFECT OF REGULATOR VALVE OPENING VARIATIONS AND AIR SPEED ON DRYING RATE, FUEL CONSUMPTION, DRYING EFFICIENCY IN ANCHIE DRYING MACHINE - Rais Rais; Mietra Anggara (Mechanical, Energy and Material (METAL), 2023)
Indonesia is a maritime country, rich in marine resources and marine biodiversity and non-biological diversity which spreads over 3,351 million km2 of sea area and 2,936 km2 of water area of the exclusive economic zone and continental shelf (BPS, 2018). The natural conditions of this vast sea are utilized by all people in Indonesia, including the people of Labuhan Bajo Village, Sumbawa. Anchovy (Stolephorus sp.) is one of the marine commodities developed as a superior economic commodity. Many efforts have been made by anchovy fishermen and collectors in an effort to maintain and develop anchovy processing, one of which is the drying process. This study aims to determine the effect of lpg gas regulator valve opening and air velocity on moisture content, fuel consumption, efficiency and drying rate of anchovy drying machine. The variables used are the variation of the regulator valve opening and the air exhaled by the fan from outside with speeds of 1.5 m/s, 2 m/s and 2.5 m/s. The results obtained in this study were that the highest drying rate was produced by the valve opening with a duration of 120 minutes with a drying rate of 0.630 g/min at an air speed of 2.5 m/s. Testing the water content by looking at the results of the anchovy samples and the results of the highest amount of water content, namely in the variation of valve opening 1 with a water content value of 19.12% at an inlet air speed of 2.5 m/s with a duration of drying time of 120 minutes. The highest efficiency value at 3/4 valve opening with a speed of 2 m/s with an inlet channel of 1 cm is 84.66%. Fuel consumption from the results of anchovy drying test with a temperature of 70 ℃ where the drying time is the fastest in accordance with the SNI quality standards for anchovy water content, namely opening the regulator valve 3/4 for 120 minutes, using 0.95 kg of gas.